Functional Characterization and Expression Analyses Show Differential Roles of Maternal and Zygotic Dgcr8 in Early Embryonic Development - Zhu, Zeyao; Liu, Yun; Xu, Wen; Liu, Taian; Xie, Yuxin; Sham, Kathy W. Y.; Sha, Ou; Cheng, Christopher H. K. (Frontiers in Genetics, 2020)
Dgcr8 is involved in the biogenesis of canonical miRNAs to process pri-miRNA into pre-miRNA. Previous studies have provided evidence that Dgcr8 plays an essential role in different biological processes. However, the function of maternal and zygotic Dgcr8 in early embryonic development remains largely unknown. Recently, we have reported a novel approach for generating germline-specific deletions in zebrafish. This germline knockout model offers an opportunity to investigate into the differential roles of maternal or zygotic Dgcr8. Although germline specific dgcr8 deletion has no influence on gonad development, maternal or zygotic dgcr8 is essential for embryonic development in the offspring. Both maternal dgcr8 (Mdgcr8) and maternal zygotic dgcr8 (MZdgcr8) mutants display multiple developmental defects and die within one week. Moreover, MZdcgr8 mutant displays more severe morphogenesis defects. However, when a miR-430 duplex (the most abundantly expressed miRNA in early embryonic stage) is used to rescue the maternal mutant phenotype, the Mdgcr8 embryos could be rescued successfully and grow into adulthood and achieve sexual maturation, whereas the MZdgcr8 embryos are only partially rescued and they all die within one week. The differential phenotypes between the Mdgcr8 and MZdgcr8 embryos provide us with an opportunity to study the roles of individual miRNAs during early development.